VISUAL ACUITY IN PATIENTS WITH STARGARDT DISEASE AFTER AGE 40. Issue 12 (December 2018) - Collison, Frederick T.; Fishman, Gerald A.
Abstract : Purpose: To better define visual acuity loss in patients with Stargardt disease later in life. Methods: The most recent best-corrected visual acuities in the better-seeing eye of 221 patients with Stargardt disease over 40 years of age were recorded. Also included were the age at subjective onset for symptoms and duration of symptoms. Juvenile onset was defined as onset before age 21; adult onset was defined as onset between 21 and 40 years; and late onset was defined as onset at age 41 or later. Results: The median age of the patients with Stargardt disease was 53.1 years. Twenty-four patients (10.9%) had worse than 20/400 best-corrected visual acuity, and none had either light perception or no light perception vision. Whereas 17 of the 52 juvenile onset patients had best-corrected visual acuity worse than 20/400, only 4 of 80 adult-onset patients and 1 of 70 late-onset patients reached this level of acuity loss. Conclusion: Although many patients with Stargardt disease lose visual acuity to the 20/200 to 20/400 range, and some lose visual acuity beyond 20/400, none of these patients reached either light perception or no light perception. The numbers found in this study will be valuable in counseling patients with Stargardt disease and could have value in planning treatment trials. Abstract : This retrospective study of visual acuity in 221 patients with Stargardt disease, between the ages of 41 and 88 years, found that 24 patients (10.9%) had worse than 20/400 Snellen acuity, and juvenile onset patients were more likely to progress to this level of visual acuity.